Analysis of the marginal adaptation of different crowns fabricated with computer-aided technology using an intraoral digital scanner - Roniel Kapler; Michelle Villa Oliveira; Ingrid de Oliveira Bandeira; Thayara Coelho Metzker; Adriana Oliveira Carvalho; Emilena Maria Castor Xisto Lima (Universidade Estadual de Campinas, 2020)
Aim: The aim of this study was to evaluate the marginal adaptation of ceramic and composite resin crowns fabricated with computer-aided design and computer-aided manufacturing (CAD/CAM) technology using an intraoral digital scanner. Methods: A human mandibular right second molar was prepared for a ceramic crown. The impressions were made using intraoral scanning device and crowns were milled. Tem crowns were fabricated for each group (n=10): GF - Feldspathic Ceramic (Cerec Blocs, Sirona), GL - Lithium Disilicate Ceramic (IPS e.max CAD, Ivoclar), GG - composite resin (Grandio Blocs, VOCO) and GB - composite resin (Brava Block, FGM). The marginal gap was measured for each specimen at 4 points under magnification with a stereomicroscope. All data were statistically analyzed using one-way ANOVA followed by the Tukey's test (α=.05). Results: The lowest marginal discrepancy value was observed in GB (60.95 ± 13.64 μm), which was statistically different from the GL (84.22 ± 20.86 μm). However, there was no statistically significant difference between these groups when compared with the other groups, GF (73.26 ±8.19 μm) and GG (68.42 ± 11.31 μm). Conclusion: It can be concluded that the composite resin presented the lowest variance compared to the lithium disilicate glass ceramic, although the marginal gap of all materials tested was within the acceptable clinical limit (120 μm).